Formulation of Confucianism in the Social Welfare System in East Asia - Yi, Il Cheong (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2018)
Scholarly assessment on Asian values particularly on Confucianism have been changed quite dramatically during the development process of East Asian countries such as Japan, Taiwan, Korea, Hong Kong, and Singapore. First, it was described as the obstructing block for the development of capitalism until the 1970s, lauded as the driving force of the rapid economic development during the 1980s and the 1990s, and then again criticised as the incubator of the crony capitalism and all the irregularities during the Asian financial crisis at the end of the last century. These different opinions on Asian values, or more narrowly, Confucianism, one of the most important factors formulating the society for thousand years, lead us to two important questions. Firstly, what is Confucianism? Although several Asian countries were deeply influenced by Confucianism, they have different cultures and traditions. They may have different ideas about Confucianism which may be quite contrary with each other. Then, is there such a thing like â€œdefinitiveâ€ Confucianism? If it is the case, how we do understand and explain Confucianism?